Evaluation of the Factors Defining the Relationship Quality in Respect of the Customer-Supplier Cooperation - Ványi, Noémi (International Journal of Engineering and Management Sciences, 2017)
The importance of the examination of customer-supplier relationship is growing on the field of supply chain management. Besides the fact that the researches in the topic of business relationship marks the quality of the as the crucial element of effective cooperation, still it can be identified as an unidentified area knowing that there is no agreement in the defining dimension. In the center in this dissertation are the dyadic business relationships. The main aim is to support the hypothesis that trust, dependence, conflict and personal relationship between the members of the supply chain are the crucial elements of the cooperation of the members of the chain and by that, they can be the defining elements of the relationship quality .As the results of my Primer research, I describe and reveal the previously mentioned dimensioned relevant for the customer and suppliers relationships in the microbusinesses producing fruits for the national, fresh market, how the good business relationship contributes to the company to reach its main goals and increase its competitiveness on the market. Based on my research, it can be stated that trust, dependence, conflict and personal relationship are the defining factors of relationship quality, moreover my results prove the fact that relationship quality contributes to the increase of the performance of the contributors.